GLOBALISASI DAN DAKWAH ISLAM KONTEMPORER - Hidayat HT (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Globalization is recognized as consciously carrying two sides of values ​​for human life, namely good values ​​and bad values. These two sides of value penetrate into all aspects of the order of life. Consequently, globalization raises many problems that plague the inhabitants of planet earth today. Among the impacts of globalization are the emergence of contemporary issues related to religion as well as challenges for Islamic da'wah, such as: religious pluralism, liberal Islam (religious liberalism), radicalism-terrorism and so on. Islam and its people who are in a global vortex and are related to several contemporary issues should come to the surface with contemporary Islamic ideas or thoughts to answer the challenge of da'wah while positioning Islam as a universal religion. Contemporary Islamic thought is thought that is able to bridge between the two poles, namely between tradition and modernity (al-turats wa al-hadatsah), so that it raises new awareness in giving birth to ideas that can respond to contemporary problems. Preaching contemporary Islamic thought like this is essentially continuing the missionary task that Allah and His Messenger ordered. Keywords: Globalization, Da'wah, Contemporary Islam